Educate the correct way of urination in western-style toilet - Satoshi Iwase (Archive of Urological Research - Peertechz Publications, 2020)
In Japan, urinary tract infections in elderly women are increasing, whereas they did not occur in the past. The increase is proportional to the increase in the number of western-style toilets.